2018
DOI: 10.1007/s11145-018-9825-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of handwriting training on fluency, spelling and text quality among third graders

Abstract: As recent studies and theoretical assumptions suggest that the quality of texts composed by children and adolescents is affected by their transcription skills, this experimental field trial aims at investigating the impact of combined handwriting/spelling training on fluency, spelling and text quality among normally developing 3rd graders (N = 175). In addition to the combined handwriting/spelling training group, the sample includes two other intervention groups, a handwriting training group and a spelling tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Previous research has found gender differences in writing where male writers often produce less writing output (Kim et al, 2015; Williams and Larkin, 2013; Cordeiro et al, 2018; Lichtsteiner et al, 2018). Therefore, gender differences were addressed in the models of analysis in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has found gender differences in writing where male writers often produce less writing output (Kim et al, 2015; Williams and Larkin, 2013; Cordeiro et al, 2018; Lichtsteiner et al, 2018). Therefore, gender differences were addressed in the models of analysis in this study.…”
Section: Discussionmentioning
confidence: 98%
“…In line with a theme that runs through primary and secondary education, female writers tend to outperform male writers in a range of writing outcomes (Berninger and Fuller, 1992; Knudson, 1995; c.f. Jones and Myhill, 2007; Williams and Larkin, 2013; Kim et al, 2015; Cordeiro et al, 2018; Lichtsteiner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This distinction is not a dichotomy. Creating a dichotomy between motor skills and language skills is potentially problematic, as it is possible that child's phonology may affect handwriting (Lichtsteiner, Wicki, and Falmann, 2018), or that the cognitive load of writing may also have an impact on handwriting (Sumner, Connelly, and Barnett, 2013). Still, the subtleties and approach taken here on writing – as a modality or discursive style – enabled to capture the multifaceted nature of literacy and contributed to examine how SLPs and SETs perceive their own disciplines, as well as those of other professionals who work in the field of literature.…”
Section: Methodsmentioning
confidence: 99%
“…Writing comprises several sequential and simultaneous language, cognitive, and motor processes, all of which demand some of the writer's limited cognitive resources. Low level processes of handwriting involve an integration and coordination of spelling knowledge, allographic representations, and the execution of fine motor movements, while higher-level processes include planning, ideation, consideration of audience, and revising (Hurschler Lichtsteiner et al, 2018). Translating ideas into written language is not a significant problem for expert writers.…”
Section: Introductionmentioning
confidence: 99%
“…They were not concerned about fluency and timed writing or writing from memory as these practices were never observed in kindergarten classrooms. Traditional handwriting lessons used to focus on legibility of handwriting and the importance and the knowhow of teaching handwriting fluency is not yet well known (Hurschler Lichtsteiner et al, 2018). A lack of opportunity to set up writing fluency skills in the elementary grades is particularly problematic because formal writing instruction is typically not offered to students after elementary school (Hier and Eckert, 2014).…”
Section: Introductionmentioning
confidence: 99%